1999
DOI: 10.1292/jvms.61.643
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations of Blood Pressure in Dogs

Abstract: ABSTRACT. Using the telemetry system, we measured the blood pressure (BP) invasively in seven adult mongrels while unanesthetized and unbound. Post-operative BP after implanting the telemetry BP transmitter showed temporarily high values due to the invasive nature of the surgery. It was, however, observed that BP gradually decreased thereafter, and showed settled trends from the eighth day postoperatively. When we took the average of the systolic, mean and diastolic BP at hourly intervals for each of the dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 20 publications
3
39
1
Order By: Relevance
“…Some studies, carried out on dogs, reported low mean BP throughout the night to early morning and high BP from early morning and throughout the day (Broten et al, 1988). Other authors (Mishina et al, 1999) have monitored the 24-h BP in dogs using telemetry and observed changes almost identical to those reported in humans (Baumgart, 1991;Mancia et al, 1993;Sundberg et al, 1988) with the highest values during periods of activity and the lowest during sleep.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Some studies, carried out on dogs, reported low mean BP throughout the night to early morning and high BP from early morning and throughout the day (Broten et al, 1988). Other authors (Mishina et al, 1999) have monitored the 24-h BP in dogs using telemetry and observed changes almost identical to those reported in humans (Baumgart, 1991;Mancia et al, 1993;Sundberg et al, 1988) with the highest values during periods of activity and the lowest during sleep.…”
Section: Introductionsupporting
confidence: 70%
“…A circadian rhythm in blood pressure has been demonstrated in various species of mammals, including rat (Van Den Buuse, 1994;Sato et al, 1995), rabbit (Sato et al, 1995), cat (Brown et al, 1997), dog (Mishina et al, 1999;Piccione et al, 2005a), cattle (Fazio et al, 2002), marmoset (Schnell and Wood, 1993) and mouse (Gross et al, 2000). Many reseachers have reported that cardiovascular indices, like sympathetic activity increase significantly during the day and decrease during the night; parasympathetic activity does the opposite (Veerman et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we employed telemetry, which allows accurate determination of blood pressure in the absence of anesthesia or constraint. We have previously demonstrated that telemetrically acquired 24-hr blood pressure is suitable for evaluating or comparing individual blood pressure in dogs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Telemetric blood pressure measurements: Blood pressure was determined by telemetric system as described previously [31]. The catheter of the transmitter for blood pressure measurement (TA11PA-C40; DATA SCIENCE INTERNATIONAL Inc., Tokyo, Japan) was indwelled within the femoral artery, and blood pressure was determined without anesthesia or constraint.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation